2016
DOI: 10.1016/j.bjm.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of housefly, Musca domestica (Diptera: Muscidae) to different entomopathogenic fungi

Abstract: The housefly Musca domestica is a worldwide insect pest that acts as a vector for many pathogenic diseases in both people and animals. The present study was conducted to evaluate the virulence of different local isolates of Beauveria bassiana, Metarhizium anisopliae and Isaria fumosorosea on M. domestica using two bioassay techniques: (1) adult immersion and (2) a bait method applied to both larvae and adults. The results showed evidence of a broad range of responses by both stages (larvae and adults) to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 33 publications
1
30
1
3
Order By: Relevance
“…After the title and abstract screening, 131 full- text articles were retrieved. Of these, a final 99 articles were identified for this review [ 2 24 , 26 – 93 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the title and abstract screening, 131 full- text articles were retrieved. Of these, a final 99 articles were identified for this review [ 2 24 , 26 – 93 ]…”
Section: Resultsmentioning
confidence: 99%
“…The use of chemical pesticides, which is the most common method today, is fast losing grounds due to the growing resistance by the house fly and other pests, couple to the effects they may have on non-target organisms [ 97 – 99 ], have led to the consideration of other methods, including biological control. Biological control agents including fungi of the genera Metarhizium and Beauveria , and bacteria including Bacillus thuringiensis can be used to control the housefly [ 93 , 97 ]. Furthermore, the sequencing of the genome of the house fly presents new opportunities for the identification of novel targets for controlling the housefly and also for understanding the mechanism of resistance to insecticides as well as the genetic adaptation of the house fly to high pathogen loads [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Petch have also shown promise . The susceptibility of M. domestica to several species of entomopathogenic fungi is well documented and multiple studies have indicated that isolates of M. anisopliae can be particularly virulent, but a mycoinsecticide product for the control of house flies based on M. anisopliae is yet to be commercially developed. Metarhizium anisopliae (BRIP #42412) has shown significant potential for house fly mycoinsecticide development as it has shown high virulence to M. domestica and exhibited high yield and germination rate through multiple production runs (Leemon DM, unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…(2012) . The captured flies were reared in transparent cages (30 cm × 30 cm × 30 cm) with mesh screens on opposite sides and a cloth sleeve opening at the front ( Farooq & Freed 2016 ) in the insect rearing room of our laboratory at 25°C–28°C, and 55%–60% relative humidity and fed a sugar/ milk solution (50 g of powdered milk and 20 g of table sugar per litre of water) ( Lohmeyer & Pound 2012 ). The eggs obtained from the captured flies were either used directly in the ovicidal bioassays or transferred to plastic Solo cups containing a semi-synthetic diet used by Kumar et al .…”
Section: Methodsmentioning
confidence: 99%